Endoscopic clipping in non-variceal upper gastrointestinal bleeding treatment - Giuseppe Galloro; Angelo Zullo; Gaetano Luglio; Alessia Chini; Donato Alessandro Telesca; Rosa Maione; Matteo Pollastro; Giovanni Domenico De Palma; Raffaele Manta (Korean Society of Gastrointestinal Endoscopy, 2022)
Since the earliest reports, advanced clipping systems have been developed, and it is possible to choose among many models with different structural and technical features. The main drawback of through-the-scope clips is their small size, which allows the compression of limited amounts of tissue needed for large-size vessel treatment. Therefore, the over-the-scope clip system was realized, allowing a larger and stronger mechanical compression of large tissue areas, with excellent results in achieving a definitive hemostasis in difficult cases. Many studies have analyzed the indications and efficacy of two-pronged endoclips and have shown good results for initial and permanent hemostasis. The aim of this review was to provide updated information on indications, positioning techniques, and results of clip application for endoscopic treatment of upper gastrointestinal non-variceal bleeding lesions.